2020
DOI: 10.26717/bjstr.2020.27.004462
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ultrasonographic Appearances in Superficial Fibromatoses: Palmar and Plantar Diseases

Abstract: Dermatologic ultrasound imaging has been rapidly growing in recently years [1,2]. Currently, ultrasonography (US) studies for superficial fibromatoses, palmar fibromatosis, namely Dupuytren's disease [3] and plantar disease, namely Ledderhose disease [4] which are located in the subcutaneous tissue have been described in ultrasound field. Dupuytren's disease is a routine for the dermatologist, because patient with subcutaneous nodule may firstly visit a dermatologist. In this review, the author provides an upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Recently, the study using the ultra-highfrequency ultrasound in the evaluation of pediatric pilomatricoma has been reported [11]. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described several reports in the dermatologic area [2,4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…Recently, the study using the ultra-highfrequency ultrasound in the evaluation of pediatric pilomatricoma has been reported [11]. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described several reports in the dermatologic area [2,4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…The author has reported a subcutaneous NF representing compressed fascia using both highresolution ultrasonography (US) and magnetic resonance imaging (MRI) appearances [4] and a rare case of intradermal type showing the primarily in the dermis accompanied by the dilatation and proliferation of the vessels using high-resolution color Doppler ultrasound [5], it is known that high-resolution US can clearly represent the location of the dermis and subcutaneous, association of the fascia, and the presence of dilation and proliferation of the vessels. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer and described several studies [4,5,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: High-resolution Ultrasonography Appearances In Nodular Fasciitismentioning
confidence: 99%
“…Enhancement pattern was heterogeneous [35]. As it is also important to differentiate between ALM and giant cell tumor of the tendon sheath (GCTTS), the author previously mentioned the characteristic appearances of GCTTS on US and MRI [20,36]. It is suggested that US study shows hypoechoic nodule with vascularity and low signal intensity on T1 and T2 weighted MR images due to the hemosiderin were observed in GCTTS [20,37].…”
Section: Reynolds Et Al Suggested That Schwannoma Have Been Classicallymentioning
confidence: 99%
“…a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described knowledge including ALM reports and several studies in the dermatologic area [2,4,[10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%